Implementasi Live Forensics untuk Perbandingan Browser pada Keamanan Email - Muhammad Nur Faiz; Rusydi Umar; Anton Yudhana (UIN Sunan Kalijaga Yogyakarta, 2017)
Digital Forensics become one popular term because Currently many violations of cyber crime. Digital techniques Computer Forensics performed or with analyze digital device, whether the device is a media Actors or as a media victim. Digital Forensic Analysis Being divided into two, traditional / dead and alive. Forensic analysis traditionally involves digital data Deposited permanent Operates in Irish, while live forensic analysis involves analysis of data Namely temporary in Random Access Memory or Deposited hearts transport equipment in the Network. Singer proposes journal Forensic analysis of life in the latest operation system windows 10. That study focused IN case several email security browsers Sales Operations manager of Google Chrome, Mozilla Firefox, and Microsoft Internet Explorer Edge. In addition, although many digital forensics type software applications not free, goal on research objectives compares browser security information so it will be more minimize abuse email.